Needs assessment for emerging oral microbiome knowledge in dental hygiene education - Wiener, R. Constance (J Epidemiol Res, 2015)
The curricula of dental hygiene education reflect the knowledge gained through research and clinical advances. Emerging knowledge is often complex and tentative. The purpose of this study is to assess dental hygiene students' confidence in their knowledge about the oral microbiome and to conduct a knowledge needs assessment for expanding their exposure to emerging knowledge about the oral microbiome. Sixty dental hygiene students were surveyed, using a Likert-type scale about their confidence and about current and emerging bacteriological research. The majority of students (60%) reported being confident in their knowledge. The mean score for the ten items was 35.2% (standard deviation, 20.6%). The results of this study indicate a need for emphasis on emerging oral microbiome research in dental hygiene education. This is important so that dental hygiene students can properly share information with their patients about advances in dental care.